7x-2(4-3x)=3(2x+1)

Simple and best practice solution for 7x-2(4-3x)=3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2(4-3x)=3(2x+1) equation:


Simplifying
7x + -2(4 + -3x) = 3(2x + 1)
7x + (4 * -2 + -3x * -2) = 3(2x + 1)
7x + (-8 + 6x) = 3(2x + 1)

Reorder the terms:
-8 + 7x + 6x = 3(2x + 1)

Combine like terms: 7x + 6x = 13x
-8 + 13x = 3(2x + 1)

Reorder the terms:
-8 + 13x = 3(1 + 2x)
-8 + 13x = (1 * 3 + 2x * 3)
-8 + 13x = (3 + 6x)

Solving
-8 + 13x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + 13x + -6x = 3 + 6x + -6x

Combine like terms: 13x + -6x = 7x
-8 + 7x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + 7x = 3 + 0
-8 + 7x = 3

Add '8' to each side of the equation.
-8 + 8 + 7x = 3 + 8

Combine like terms: -8 + 8 = 0
0 + 7x = 3 + 8
7x = 3 + 8

Combine like terms: 3 + 8 = 11
7x = 11

Divide each side by '7'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| 5+7x-3x=-27 | | 3x+w=8x+v | | 53350-75h+200h=55825-150h | | 2n(n+5)= | | 7.2y+3=3y+21 | | 6-6x-3=-46+3x-14 | | -3x^2+246x-1100=0 | | 200M-75m+53350=55825-150m | | a^2+3a= | | 2e+2.6=-23 | | 7(9w)= | | 6(v+4)-2v=2(2v+1)-7 | | X+6-4x=21 | | (3x-10)+(x+40)=90 | | -4+3x+1=5x+2 | | -5-=0 | | -4x-10=7x+23 | | -18=14 | | -x-4y=-3 | | 2(xy+4)=-7 | | (3x-10)+(x+40)=120 | | 6(2b)= | | 3a-8=2(e-4) | | 6x-15-3x=5x-8 | | (3x-10)+(x+40)=60 | | x^2+7x-4x-28= | | -8x+9+4x=41 | | 40m=L | | 5+2x/4=-7x | | 3x+9-1.5x=17-0.5x | | 7b^2+9b=0 | | 11.6=1.5s |

Equations solver categories